Socio-Economic and Demographic Factors Associated with Raw Alcohol Consumption - Zain Ul Abidin Abbasi, Muhammad Ilyas Siddiqui, Gulzar Usman, Sikander Munir Memon, Aftab Haider Deeshak, Mahesh K. Luhana (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the socioeconomic and demographic characteristics that influence raw alcohol intake. Methods: It was a cross sectional study, conducted at community level at Badin district for 3 months from 1st September 2019 to 30th November 2019. The study included all of the cases that met the inclusion criteria. All responders or their relatives provided written consent. A complete history of alcohol intake and associated factors was obtained. Performa was used to record all of the data. For data analysis, the SPSS v.22 was utilized. Results: A total of 115 individuals participated in the study. Their mean age was 37.11 years, with a standard deviation of 8.096. The majority of the individuals (89.6%) were Sindhi; in terms of religion, 43(37.4%) were Muslin, 6(55.7%) were Hindu, and 8(7%) were Christians; roughly 53(46.1%) of the study participants were illiterate and had no education. About 44.3% started to drink as an adult, 26.1% drank more than five times per day, 61.7% drank more than two pegs/glasses of raw alcohol on a daily basis, % liked to drink at night, and around 45.2 % drank alcohol as a habit. The majority of drinkers (46%) were encouraged by their friends. Practical implication From point of practical implication, it is important to know that drinking alcohol increases the chance of developing mental and behavioral disorders, including alcohol dependency, as well as severe non-communicable illnesses such as liver cirrhosis, several malignancies, and cardiovascular disease. Conclusion: Raw alcohol intake (ethanol) can have major effects for people’s current and future health and quality of life; our findings give critical new information regarding this public health issue. Keywords: Alcoholism, Consumption, Demographic factors, Ethanol, Raw alcohol.